Electrochemical Strategies for the Screening of Synthetic Cannabinoid BB-22 (QUCHIC) within a Toxicological Specimen. Issue 12 (10th December 2021) - Ameen, Anaam; Brown, Kelly; Dennany, Lynn
Abstract : Synthetic Cannabinoids (SC) are amongst the most prevalent class of novel psychoactive substances (NPS) which have emerged. The increase in hospitalisation and fatalities as a result of the prevalence of these SC and their abuse, highlights the necessity for the rapid and reliable screening for the substance within toxicological samples. Being able to rapidly screen for these substances would aim to improve overdose triage and ultimately improve treatment administration. Not only this but it would have further advantages for in-field applications such as the identification of drivers under the influence. To this avail we investigate the ability of a simple electrochemical screening strategy for the detection of SC, BB-22 and its primary metabolite BB-22-3-Carboxyindole. Assessment of the feasibility of the strategy for implementation into toxicological sample analysis was performed through detection not only under ideal electrolyte conditions (down to 5 μ M for BB-22 and 2 μ M for its metabolite) but also within the complex biological matrix of human pooled serum (between 200 and 700 μ M), a relevant matrix it would likely encounter if employed within this field.